Research on thermal runaway and gas generation characteristics of NCM811 high energy density lithium-ion batteries under different triggering methods - Chunjing Lin; Hongtao Yan; Chuang Qi; Jingbo Mao; Li Lao; Yazhou Sun; Tianyi Ma; Dinghong Liu (Case Studies in Thermal Engineering)
Safety concerns, including thermal runaway and gas generation, present significant challenges for high-energy-density lithium-ion batteries. Thermal abuse, a common trigger for thermal runaway, can be induced by various methods, including heating rods, coils, plates, and lasers. This study compares the impacts of three heating techniques—heating rods, coils, and plates—on thermal runaway and gas generation in a commercially used NCM811 lithium-ion battery, which has a high energy density of 280.24 Wh/kg (the latest cylindrical 46950 model). The study found that the heating coil was the most effective, triggering thermal runaway more quickly and at a higher temperature than the heating plate and rod. Gas production analysis revealed that the heating coil method generated significantly more gas, particularly CO2, than the other methods. The concentrations of gases produced during thermal runaway (CO, CO2, H2, and CH4) varied by heating method, with the heating coil leading to a more complete battery reaction. The safety evaluation highlighted the hazardous nature of the heating rod method, which produced the widest flammable gas concentration range and the highest explosion risk among the tested heating methods. This study provides critical insights into heating techniques in lithium-ion battery thermal runaway scenarios and offers valuable data for improving safety measures in energy storage systems.